ANALYSIS OF THE EFFECT OF THE USE OF INFORMATION SYSTEMS OF REGIONAL MANAGEMENT (SIMDA) ON ASSET MANAGEMENT IN EAST ACEH DISTRICT GOVERNMENT - Iqlima Azhar; Rizka Rizka (International Journal of Economic, Technology and Social Sciences (Injects), 2020)
This study aims to examine the effect of information systems on asset management in the East Aceh District Government. The research was carried out on employees of the goods section of the East Aceh District Government Offices. Determination of the sample used in this study is the census method with a total sample of 44 people. The results showed that there is a significant relationship between information systems on asset management.